Finansowoprawne podstawy inwestycji zagranicznych w Polsce - Małecki, Jerzy (Wydział Prawa i Administracji UAM, 1990)
Polish economy requires to be restructured in the direction of the market system of highly developed countries. One of the steps along this way is a radical change of Polish financial legislation. A successful implementation of the programme of economic and legal reform would make Poland more attractive for foreign investors. At present a legal framework for foreign entreprises and foreign investment are the Acts of 1982 and 1988. Foreign units are protected from unfavourable changes in the spheres of income tax, transfer of profits and nationalization by guarantee clauses. The article presents legal-financial constructions in the field of foreign investment (taxation, customs, currency and credit regulations) and comments on the future direction of changes.
Legal-financial basis for foreign investment in Poland